Using information technology to share experiences and enhance communication skills 2006-2009 - Looy, Anne de (2011)
This report follows the unique exchange of information across Europe that took place through visits conducted as part the EU-funded Thematic Network ‘Dietitians Implementing Education and Training Standards’ in Europe (DIETS). A great deal of learning and change to practice was anecdotally reported from the face-to-face visits. These will take time to implement following focussed reflection. This report attempts to capture some of these reflections. Reflection across great distances was an environmental and resource challenge. The meetings were therefore conducted ‘virtually’ using information technology available to the Partners. This had the added advantage of improving further the ITC skills of the Partners. Finally, students were encouraged to undertake joint meetings or seminars and these are also reported. Using ITC successfully, and building the confidence of Partners, has increased the capabilities of the Network of HEIs and their dietetic practice placement colleagues. These improvements will endure long after the DIETS Network has finished its work. The ultimate benefit to the dietitians, through education, lifelong learning and their contribution to nutritional health in Europe will continue to unfold.